2018
DOI: 10.3390/s18113632
|View full text |Cite
|
Sign up to set email alerts
|

Optical Fibre-Based Pulse Oximetry Sensor with Contact Force Detection

Abstract: A novel optical sensor probe combining monitoring of blood oxygen saturation (SpO2) with contact pressure is presented. This is beneficial as contact pressure is known to affect SpO2 measurement. The sensor consists of three plastic optical fibres (POF) used to deliver and collect light for pulse oximetry, and a fibre Bragg grating (FBG) sensor to measure contact pressure. All optical fibres are housed in a biocompatible epoxy patch which serves two purposes: (i) to reduce motion artefacts in the photoplethysm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 29 publications
(32 reference statements)
0
25
0
Order By: Relevance
“…Rothmaier et al [200] have demonstrated such a system, using a cotton glove with woven POFs positioned at a fingertip of the glove. To improve the reliability of reflectance oximeters Liu et al [201] demonstrated a novel optical fiber sensor probe for simultaneously monitoring the photoplethysmogram and contact pressure to provide reliable blood oxygen saturation monitoring. This probe combined a reflectance pulse oximeter with a fiber Bragg grating contact pressure sensor and enables more comfort of the user because it can be used in loosely fitting garments and the measurements can only be recorded when appropriate pressure is applied.…”
Section: Monitoring Of Blood Oxygen Saturationmentioning
confidence: 99%
“…Rothmaier et al [200] have demonstrated such a system, using a cotton glove with woven POFs positioned at a fingertip of the glove. To improve the reliability of reflectance oximeters Liu et al [201] demonstrated a novel optical fiber sensor probe for simultaneously monitoring the photoplethysmogram and contact pressure to provide reliable blood oxygen saturation monitoring. This probe combined a reflectance pulse oximeter with a fiber Bragg grating contact pressure sensor and enables more comfort of the user because it can be used in loosely fitting garments and the measurements can only be recorded when appropriate pressure is applied.…”
Section: Monitoring Of Blood Oxygen Saturationmentioning
confidence: 99%
“…It has a Young's modulus (137.9 MPa) lower than that of the optical fibre, which increases the strain induced on the FBG under a transverse load [33,34]. FBGs are also sensitive to temperature, and so a second FBG (FBG2) is used for temperature compensation [25]. The FBG2 is located inside a stainless-steel tube (internal diameter = 0.31 mm) in order to isolate it from the effects of pressure [35,36].…”
Section: Crt Monitoring Systemmentioning
confidence: 99%
“…The pressure sensor consists of two FBGs which are fabricated in the core of the same silica fibre (PS1250, Fibercore Ltd., Hampshire, UK). One FBG (FBG1) was covered by epoxy in order to increase the pressure sensitivity, whilst the other FBG (FBG2) was applied to compensate for the temperature effect on FBG1 [25].…”
Section: Fbg Calibration and Validationmentioning
confidence: 99%
See 2 more Smart Citations